If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 3 = 2x + 58 Reorder the terms: 3 + 7x = 2x + 58 Reorder the terms: 3 + 7x = 58 + 2x Solving 3 + 7x = 58 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 7x + -2x = 58 + 2x + -2x Combine like terms: 7x + -2x = 5x 3 + 5x = 58 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 5x = 58 + 0 3 + 5x = 58 Add '-3' to each side of the equation. 3 + -3 + 5x = 58 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = 58 + -3 5x = 58 + -3 Combine like terms: 58 + -3 = 55 5x = 55 Divide each side by '5'. x = 11 Simplifying x = 11
| -16(t^2-361)=0 | | 0.3(3n-5)=0.4-0.2(n-7) | | (q-5)*2=10 | | 12xX=72 | | a-52=112 | | (q-8)*3=6 | | X^2=5x+8 | | c=15+4*9 | | c=15+4*8 | | c=15+4*7 | | x-10=70-7x | | (e+1)*5=10 | | c=15+4*50 | | 2(z+2)-5=7 | | X^2y+3xy+xy^2=0 | | 2x^2-4x^3+12x-6=0 | | 500x-x=300 | | -5x+5=6-4x | | 2+2x=4x-14 | | 3(0--16)= | | -6x+8=20-10x | | 3(1+x)=14-x | | -3(1+x)=14-r | | -1+4x=-3x-85 | | 2x-24=3x+4 | | 1/2(x-8)-6=24 | | 2a-3b=-8 | | 5a+6b=-2 | | 6a+b=-2 | | 3x-8=-2-3x | | -5r-5s=25 | | b+14=56 |